Premis Kampus Merdeka: Perspektif Budi Rahardjo - Ahmad Firdaus Suryo Saputro; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to find out about independent campuses according to. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from Budi Rahardjo's YouTube channel entitled "About the Independent Campus: BR's Opinion" which he presented. The results of this study explain about the independent campus program, there are many problems that must be solved by the Independent Campus program, such as gaps in the knowledge and skills of college graduates. Then a new problem emerged, namely that many parties used it to make money (business education). Education in Indonesia is listed in Law no. 20 of 2003. To achieve educational goals, a curriculum is needed that makes the educational process easier. Nadiem Makarim is the Minister of Education and Culture who initiated the Independent Learning Campus (MBKM) curriculum. The concept of independent learning aims to liberate education through free thinking and free innovation. The MBKM program is often promoted, but not many academics or practitioners understand this concept. For this reason, further introduction is needed to deepen insight into MBKM.